СРОЧНО! помогите пожалуйста!!! Упростите выражение:(а-2)(а-2)(а^2+4)(а^4+16)-(а^4-1)^2 =

0 голосов
37 просмотров

СРОЧНО! помогите пожалуйста!!!
Упростите выражение:


(а-2)(а-2)(а^2+4)(а^4+16)-(а^4-1)^2 =


Математика (41 баллов) | 37 просмотров
0

я немного ошиблась)

0

(а-2)(а-2)(а^2+4)(а^4+16)-(а^4-1)^2 =

0

минуту тогда

0

*_*

0

:(

0

эхххх

0

ну что?

0

не как?

0

или решаеться?

0

Спасибо*******

Дан 1 ответ
0 голосов
Правильный ответ

Решите задачу:

(a-2)(a-2)(a^2+4)(a^4+16)-(a^4-1)^2 =\\\\=(a^2-4a+4)(a^6+16a^2+4a^4+64)-a^8+2a^4-1=\\\\=a^8+16a^4+4a^6+64a^2-4a^7-64a^3-16a^5-256a+4a^6+64a^2+\\\\+16a^4+256-a^8+2a^4-1=-4a^7+8a^6-16a^5+34a^4-64a^3+\\\\+128a^2-256a+255
(30.1k баллов)